The Effect of Banking Channels and Efficiency Indicators on Bank Profitability - Magallón González, Heber Bernardo; Galeana Figueroa, Evaristo; de la Torre-Torres, Oscar Valdemar (Mercados y Negocios, 2023)
This article proposes two models to analyze profitability banking. Using panel data methodology, it examined the relationship between operational efficiency indicators and banking access channels alternative to the branch with ROA and ROE. The main findings are that Net Operating Margin (MNO) has a direct relationship. Net noninterest Margin (MNNI) and Asset Utilization (RA) have a negative impact on ROA. Regarding access channels, Automatic Teller Machines (ATMs) have a positive, albeit weak, impact. Point of Sale Terminals (POS) are significant but in reverse. As for ROE, MNO and MNNI are related in the same sense as ROA. The Capital Multiplier (MC) presents a negative relationship. Mobile Banking (NBM) and POS show a significant inverse relationship, while ATM is direct.